Experiences of COVID-19 survivors and their families: A qualitative study based on social cognitive theory - Malihe Sohrabivafa; Roya Sadeghi; Yaser Tedadi; Shirin Shahbazi Sighaldeh; Forough Riahi; Abbas Rahimi Foroushani; Javad Zarei (Journal of Education and Health Promotion)
BACKGROUND: The COVID-19 pandemic caused social and economic damages, increased mortality rates, and psychological damages such as fear, stress, anxiety, and depression. Therefore, the present study aimed to explore the perceptions and experiences of COVID-19 survivors diagnosed with anxiety and depression, along with one of their family members in Ahvaz. MATERIALS AND METHODS: A qualitative study was conducted on 50 COVID-19 survivors and their family members using an in-depth interview and a purposive sampling method in 2022. On average, each interview lasted 45 minutes. For the content analysis, the content of the interviews was analyzed using MAXQDA10 software. RESULTS: In the present research, 188 primary codes were extracted with six categories and eight subcategories for the survivors: Patient’s knowledge and perspective regarding COVID-19, post-COVID-19 conditions, sense of capability before and after infection with COVID-19, management of COVID-19, and social support, and one main category for family members: social support. CONCLUSION: The experiences of COVID-19 survivors, their friends, family members, and healthcare providers significantly impact their mental health and accelerate their recovery. Therefore, it is recommended to develop an educational and preventive program using scientific and proper methods to cope with psychological challenges.